International transport corridors in South Asia: geopolitical problems - Shcharbina, Yury A. (Journal of the Belarusian State University. International Relations, 2023)
The difficulties and geopolitical constraints for international transport corridors in South Asia are studied. The present barriers to their operation and expansion, such as infrastructural deficits, political instability, and geopolitical restraint are discovered. The impact of geopolitics on regional trade and economic development is also discussed, along with the contribution of regional and global players to the resolution of security and stability issues. A review of the intricate geopolitical dynamics of the transit corridors revealed significant issues and conflicts amongst the states in the region. Opportunities are identified for the Eurasian Economic Union to reroute its cargo flows in response to Western sanctions presented by the International North – South transport corridor, Indian projects “Act East” and “Neighbourhood first”, and the China – Pakistan economic corridor.
Keywords: South Asia; Pakistan; India; international relations; geopolitics